Determinants of dividend policy in Malaysian stock markert / Norhasmimi Nasir - Nasir, Norhasmimi (2017)
The purpose of this study is to investigate on the determinants of dividend policy in Malaysia stock market. There are 30 public listed companies are selected randomly from Bursa Malaysia main market. The period of the present study is from 2011 until 2015. The data has been collected randomly from various sectors in Malaysia such as consumer, construction, finance, trading and service, plantation and properties. The dividend policy has been chosen as dependent variable while board size, CEO duality, board activity intensity, firm size, growth, profitability, lag dividend 1 and lag dividend 2 have been chosen as independent variables in this study. Based on the findings, by using multiple regressions, five variables that are significant which are CEO duality, log firm size, log growth, log profitability and lag dividend 1. Otherwise, board size, board activity intensity and lag dividend 2 are insignificant. Based on F-statistics it was found that all variables are significant influences dividend policy in Malaysia at 1%. In short, the study found that corporate governance and dividend policy in Malaysia can be explained by CEO duality, log firm size, log growth, log profitability and lag dividend 1for the period 2011 until 2015